War Ethics in Islam and the West: A Case Study of the Israel-Palestine Conflict - Shaukat Zaman; Dr. Badshah Rehman; Dr. Aziz Ahmad (Al Manhal Research Journal, 2025)
The world and its all nations desire peace and security. Naturally everyone prefers peace and no human being would want a situation where war and conflict break out. However, historically it is also true that clashes of power, politics, and ideologies have always existed, because which many wars have been witnessed. However, even during wars, there are some fundamental moral norms and human values that are acknowledged globally. These principles and values aim to reduce human suffering and to ensure humane treatment of opponents even in times of wars. Islam presents a complete system of life. Even in war, it lays great emphasis on morality and values. On other hand, the West also formulated rules and laws of wars through the Geneva Conventions and various other agreements. The current Israel-Palestine conflict has once again raised questions about human rights and ethical standards during war. Attacks on urban populations, civilians settlements, places of worship, children, women, journalists, aid workers, and medical personnel, is the violation of international laws and Islamic teachings. In this article, comparison between Islamic and western war ethics will be presented, especially Israel brutalities in Palestine so it becomes clear which ideology (Islamic or western) upheld humanity during the war and who failed in the face of ground realities.